2012
DOI: 10.1016/j.yebeh.2012.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Default mode network abnormalities in idiopathic generalized epilepsy

Abstract: Idiopathic Generalized Epilepsy (IGE) is associated with widespread cortical network abnormalities on electroencephalography. Resting state functional connectivity (RSFC), based on fMRI, can assess the brain’s global functional organization and its disruption in clinical conditions. We compared RSFC associated with the ‘default mode network’ (DMN) between people with IGE and healthy controls. Strength of functional connectivity within the DMN associated with seeds in the posterior cingulate cortex (PCC) and me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
90
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(108 citation statements)
references
References 38 publications
17
90
0
1
Order By: Relevance
“…We also hypothesized that people with GE would have inadequate suppression of DMN during language processing expressed by abnormal task-related functional DMN segregation, in line with the recent resting-state findings by McGill et al [22]. Finally, we also hypothesized that adding complexity to the sentence reading task would induce a further reduction of the BOLD response in DMN, according to previous findings in the literature [29].…”
Section: Introductionsupporting
confidence: 77%
See 3 more Smart Citations
“…We also hypothesized that people with GE would have inadequate suppression of DMN during language processing expressed by abnormal task-related functional DMN segregation, in line with the recent resting-state findings by McGill et al [22]. Finally, we also hypothesized that adding complexity to the sentence reading task would induce a further reduction of the BOLD response in DMN, according to previous findings in the literature [29].…”
Section: Introductionsupporting
confidence: 77%
“…By inspection of Figure 1, we tentatively suggest that GE participants had a global deficiency to suppress DMN. Thus, a possible explanation of the result is that there is a reduced functional segregation of DMN in GE, as proposed by McGill et al [22]. This reasoning is supported by the observed significant difference between GE participants and controls in the posterior cingulate cortex, as this region is suggested to be a central node in DMN with strong interactions to other nodes of the network [47].…”
Section: Inadequate Negative Bold Responsesupporting
confidence: 54%
See 2 more Smart Citations
“…In addition to the abnormal network of epileptic foci described above, RS-fMRI studies have also found decreased functional connectivity in the attentional [53] , perceptual [54] , and default mode networks [55,56] , as well as subcortical regions [57,58] . These results indicate that abnormal synchronization is widespread in mTLE patients.…”
Section: Functional Connectivity Based On Linear Correlationmentioning
confidence: 88%